Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1038/sj.bjp.0702463
|View full text |Cite
|
Sign up to set email alerts
|

Functional comparison of muscarinic partial agonists at muscarinic receptor subtypes hM1, hM2, hM3, hM4 and hM5 using microphysiometry

Abstract: 1 This study describes the pharmacological comparison of the muscarinic partial agonists sabcomeline, xanomeline and milameline at human cloned muscarinic receptor subtypes (hM 1 ± 5 ). 2 Radioligand binding studies at the hM 1 ± 5 muscarinic receptor subtypes were compared with functional studies using microphysiometry using carbachol as the standard full agonist. 3 In binding assays none of the compounds studied displayed preferential a nity for the M 1,3,4 or M 5 subtypes although carbachol was less potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
41
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 16 publications
(18 reference statements)
10
41
0
Order By: Relevance
“…Using M 1 mAChR calcium mobilization assays as described previously, all four compounds demonstrated positive allosteric modulation of the ACh-induced receptor response and no observed allosteric agonism in their own right. The most substantial enhancements of ACh potency were reported for VU0029767 (25) (15-fold) and VU0119498 (22) (14-fold). Unfortunately, none of the test compounds showed absolute subtype selectivity for the M 1 mAChR.…”
Section: ■ M 1 Machr-selective Ligandsmentioning
confidence: 93%
See 1 more Smart Citation
“…Using M 1 mAChR calcium mobilization assays as described previously, all four compounds demonstrated positive allosteric modulation of the ACh-induced receptor response and no observed allosteric agonism in their own right. The most substantial enhancements of ACh potency were reported for VU0029767 (25) (15-fold) and VU0119498 (22) (14-fold). Unfortunately, none of the test compounds showed absolute subtype selectivity for the M 1 mAChR.…”
Section: ■ M 1 Machr-selective Ligandsmentioning
confidence: 93%
“…20 This antipsychotic action is postulated to occur via indirect modulation of dopamine levels; the M 4 mAChR is highly expressed within the mesolimbic dopaminergic system, commonly associated with positive symptoms of schizophrenia. 21 Unfortunately, while xanomeline exhibits some degree of selectivity as a M 1 /M 4 mAChR agonist, binding studies in cloned human muscarinic receptors revealed no preferential binding affinity for these two subtypes in relation to the others, 22 a factor that likely contributed to the peripheral cholinergic side effects that prompted the withdrawal of 52% of AD subjects in a phase III trial of xanomeline. 9 This, combined with its vastly different efficacy and selectivity profiles depending on the in vitro experimental paradigm utilized, 15 its off-target activity at dopaminergic and 5-HT receptor subtypes, 23 and the compound's metabolic instability and high hepatic first pass effect leading to <1% oral bioavailability in both animals and humans, 15 has rendered xanomeline an insufficient clinical candidate.…”
Section: ■ the Cholinergic Hypothesis Of Memory Dysfunctionmentioning
confidence: 99%
“…The mAChR agonists developed to date, such as xanomeline and sabcomeline, improve cognition preclinically, although evidence of clinical efficacy has been confounded by peripheral effects such as sweating, nausea and diarrhoea, which are believed to be attributed to the relatively non-selective mAChR activity profile of these compounds (Wood et al, 1999). This lack of selectivity is believed to be due to binding to the orthosteric ACh binding site that is highly conserved across the mAChR family (Spalding et al, 1994;Baldwin et al, 1997;Gether, 2000;Lu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of distribution suggests that this mAChR subtype may play a role in cognition. Indeed, certain molecules that are reported as being functionally selective M 1 mAChR agonists, such as xanomeline, sabcomeline and milameline, are effective in several preclinical models of cognition (Bodick et al, 1997;Harries et al, 1998;Dean et al, 2003;Weiner et al, 2004), although it must be noted that the absolute degree of selectivity of these molecules for M 1 receptors is dependent on the assay system used (Wood et al, 1999). In addition, there is early pre-clinical evidence to suggest that mAChR antagonists (Hagan et al, 1987) as well as lesioning of cholinergic projections in the forebrain of rats (Hagan et al, 1988;Smith, 1988) cause broad-ranging cognitive impairment.…”
mentioning
confidence: 99%
“…In spite of its functional selectivity for the M 1 and M 4 muscarinic receptors (Shannon et al, 1994;Ward et al, 1995;Bymaster et al, 1997Bymaster et al, , 1998, xanomeline does not discriminate in its binding affinity among all five subtypes of muscarinic receptors Watson et al, 1998;Wood et al, 1999). However, there is no information about whether xanomeline persistently binds to non-M 1 receptor subtypes, particularly those at which xanomeline exhibits low or no efficacy; e.g., the M 5 receptor.…”
mentioning
confidence: 94%